2022
DOI: 10.1001/jamaoto.2021.4555
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Outpatient Symptom Management in Patients With Head and Neck Cancer

Abstract: IMPORTANCEPatients with head and neck cancer manage a variety of symptoms at home on an outpatient basis. Clinician review alone often leaves patient symptoms undetected and untreated. Standardized symptom assessment using patient-reported outcomes (PROs) has been shown in randomized clinical trials to improve symptom detection and overall survival, although translation into real-world settings remains a challenge. OBJECTIVE To better understand how patients with head and neck cancer cope with cancer-related s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…One possible reason for poor symptom management is that there are still some wrong perceptions of symptom management in both patients and oncology clinicians, such as the belief that symptoms are necessary consequences of cancers and cancer treatments, and symptom management may affect the anticancer treatments negatively. 15 , 28 , 29…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for poor symptom management is that there are still some wrong perceptions of symptom management in both patients and oncology clinicians, such as the belief that symptoms are necessary consequences of cancers and cancer treatments, and symptom management may affect the anticancer treatments negatively. 15 , 28 , 29…”
Section: Discussionmentioning
confidence: 99%
“…Among patients endorsing depressive symptoms on the ESAS, less than one-fifth receive support . In our own qualitative work published earlier in 2022, patients with HNC described feeling disempowered and disengaged from symptom monitoring programs because of the inconsistent review and action on high symptom scores …”
Section: Discussionmentioning
confidence: 90%
“…Additionally, randomized clinical trial evidence supports the use of patient-reported outcome-based symptom monitoring as a method to reduce ED/Hosp and improve oncologic outcomes . The challenge is translating these results into real-world settings, where patient-reported outcome data are less consistently reviewed and acted on . In Ontario, there remains substantial room for improvement on this front.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence tools are being deployed so that limited resources can be directed to those most in need 54 . HNC survivors have been interviewed to gain their perspective on what an enhanced psychosocial care pathway might look like 55 . Existing psychiatry and psychology resources are being expanded to better address the current unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…54 HNC survivors have been interviewed to gain their perspective on what an enhanced psychosocial care pathway might look like. 55 Existing psychiatry and psychology resources are being expanded to better address the current unmet need.…”
Section: Discussionmentioning
confidence: 99%